A Digitization Advancement Model for Informal Retail in Developing Economies - Habeeb Ilufoye,; Oluwatolani Vivian Akinrinoye,; Chinelo Harriet Okolo, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Informal retail plays a critical role in the economic and social fabric of developing economies, providing livelihoods, consumer access, and community resilience. Yet, this sector remains largely excluded from digital transformation agendas due to infrastructural deficits, limited digital literacy, and institutional fragmentation. This paper proposes a conceptual model for phased, inclusive, and context-sensitive digitization of informal retail systems. Drawing on theoretical foundations from ICT for development, platform ecosystems, and stakeholder inclusion, the model outlines a three-stage pathway: adoption of entry-level digital tools; capability building through modular training; and data formalization, enabling access to credit, value chains, and market intelligence. The framework emphasizes the importance of ecosystem partnerships between fintechs, NGOs, telecoms, and tech developers in designing interoperable and locally relevant digital platforms. It also addresses the strategic enablers of equitable digitization, including infrastructure access, governance safeguards, and ethical considerations. The model’s implications are far-reaching: it aligns with broader development goals such as financial inclusion, urban resilience, and micro-enterprise growth. Moreover, it provides a scalable foundation for future innovation in AI-enabled tools, decentralized retail platforms, and participatory data governance. In reframing informal retail as a site of digital empowerment, the paper offers a roadmap for sustainable and inclusive economic transformation in the digital age.
Keywords: Informal Retail; Digital Inclusion; ICT for Development; Platform Ecosystems; Financial Empowerment; Data Sovereignty